La musicoterapia en la atención de estudiantes con comportamientos disruptivos - Infante Córdova, Mylena Pilar (2024)
Music can stimulate various brain areas, promoting cognitive and sensory development. This can be beneficial for students with behavioral disorders, as it offers them a way to actively and positively engage in the educational process. This study's objective was to analyze music therapy's contribution to the care of students with disruptive behaviors at an academic institution in Guayaquil. The research was aligned with the qualitative methodological approach, with a descriptive scope, among the techniques and instruments applied was the observation sheet applied to the students with disruptive behaviors and the teacher tutor, an interview with open questions directed to the music teacher and the DECE staff. , made up of a psychologist and a psychopedagogue. The results obtained were that the students, despite the strategies applied by the DECE, have not been able to overcome their disruptive behaviors, the tutor teacher is unable to work with them in the classroom, the interaction and the teachinglearning process are difficult, and the students chaotic the classroom. The music therapy teacher does not know many music therapy methods to work with students with specific educational needs, he provides the class with those he normally works with. The DECE staff values the importance and need of music therapy applied to cases of students with disruptive behaviors, but they do not achieve positive results with the students due to a lack of continuity in the strategies that parents must apply at home, and because teachers They are not very qualified with this educational need either. It is concluded that music becomes a tool that regulates emotions, allowing the student to manage or channel them, this contributes to improving verbal and non-verbal communication within the educational context.